SRSF2 mutations in 275 cases with chronic myelomonocytic leukemia (CMML) - Meggendorfer, Manja (American Society of Hematology, 2012)
We analyzed the mutational hotspot region of SRSF2 (Pro95) in 275 cases with chronic myelomonocytic leukemia (CMML). In addition, ASXL1, CBL, EZH2, JAK2V617F, KRAS, NRAS, RUNX1, and TET2 mutations were investigated in subcohorts. Mutations in SRSF2 (SRSF2mut) were detected in 47% (129 of 275) of all cases. In detail, 120 cases had a missense mutation at Pro95, leading to a change to Pro95His, Pro95Leu, Pro95Arg, Pro95Ala, or Pro95Thr. In 9 cases, 3 new in/del mutations were observed: 7 cases with a 24-bp deletion, 1 case with a 3-bp duplication, and 1 case with a 24-bp duplication. In silico analyses predicted a damaging character for the protein structure of SRSF2 for all mutations. SRSF2mut was correlated with higher age, less pronounced anemia, and normal karyotype. SRSF2mut and EZH2mut were mutually exclusive, but SRSF2mut was associated with TET2mut. In the total cohort, no effect of SRSF2mut on survival was observed. However, in the RUNX1mut subcohort, SRSF2 Pro95His had a favorable effect on overall survival. This comprehensive mutation analysis found that 93% of all patients with CMML carried at least 1 somatic mutation in 9 recurrently mutated genes. In conclusion, these data show the importance of SRSF2mut as new diagnostic marker in CMML.